The threat of piracy on maritime transportation. (8th April 2010) - Elbeck, Matt; Tirtiroglu, Ercan
Recent acts of piracy in and about the Gulf of Aden undermine the safe passage of crude oil critical to global economies, serving as a force majeure for logistics service providers and supply chain managers to address this menace. In contrast to the raft of diplomatic and military responses to date, this note considers hitherto unexplored approaches to bypass threats of maritime piracy by considering a transportation triumvirate of cost efficiency, intact delivery of cargo and human safety. A review of the literature is followed with an outline of the costs associated with maritime piracy on vessel and crew and concludes with methods to approach the maritime piracy problem based on risk and game theory to consider alternative routes, offering vessel, crew and cargo safety and delivery security guarantees as a result of balancing financial returns against least adverse effects by focusing on delivery assurance in lieu of delivery costs.